Sustainability Committee And Environmental, Social And Governance (ESG) : A Systematic Literature Review - Chow Kah Yong; Ervina Alfan; Mohd Zulkhairi Mustapha (International Journal of Business and Society, 2024)
The objective of this study is to provide a comprehensive systematic literature review (SLR) of the empirical studies on the impact of sustainability committee (SC) and SC’s characteristics on ESG issues. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method, 34 papers published between 2017 and 2023 were selected from the Web of Science and Scopus databases. The majority of the existing literature explored this topic in a cross-country context, with a particular focus on stakeholder theory. It was further found that empirical studies extensively focused on the presence of SC in relation to ESG; while less emphasis was placed on the characteristics of SC. While SC size and independence are the most commonly studied characteristics, it is also essential for future studies to further examine how other SC characteristics, such as gender diversity, expertise, and education, can exert an influence on ESG matters. Notably, there is a significant methodological gap. In addition, limited studies adopt qualitative and/or mixed methods in examining this relationship. Finally, the paper provides future research opportunities related to SC and ESG issues and identifies gaps in knowledge.